2008
DOI: 10.2174/1875036200802010072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Studies on NADP-Dependence of Candida Tropicalis Strain Xylose Reductase

Abstract: Abstract:The Candida tropicalis strain CT1799 xylose reductase (XR) with protein ID ABG49458.1 is a kind of NADPH-dependent xylose reductase. It could be used to construct recombinant Saccharomyces cerevisiae strain for utilizing xylose and producing alcohol. To investigate the interaction mechanism of XR with NADP and NAD, the 3D (dimensional) structure for XR was developed. With the 3D structure, the molecular docking operations were conducted to find the most favorable bindings of XR with NADP and NAD. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
5
0
1
Order By: Relevance
“…For further information about protein folding, refer to a recent review [214] and the references cited therein. Again, although it is quite successful to predict the 3D structure of a protein according to the homology modeling approach [2,215] as reflected by a series of homology-modeled proteins for drug development [84,147,[149][150][151]153,[216][217][218][219][220][221][222][223][224][225][226], a hurdle exists when the query protein does not have any structure-known homologous protein in the existing databases [3].…”
Section: Pfp-predmentioning
confidence: 99%
“…For further information about protein folding, refer to a recent review [214] and the references cited therein. Again, although it is quite successful to predict the 3D structure of a protein according to the homology modeling approach [2,215] as reflected by a series of homology-modeled proteins for drug development [84,147,[149][150][151]153,[216][217][218][219][220][221][222][223][224][225][226], a hurdle exists when the query protein does not have any structure-known homologous protein in the existing databases [3].…”
Section: Pfp-predmentioning
confidence: 99%
“…Molecular dynamics simulation is a good tool to deal with this problem. This kind of approach has been successfully applied to deal with various important biological problems (see, e.g., Wang et al, 2008aWang et al, , 2008bWang et al, , 2009bWang et al, , 2009cWang et al, , 2008cWang et al, , 2008dWang et al, , 2009dWang et al, , 2009e, 2007, particularly in utilizing it for in-depth studies of the mechanistic mechanism of M2 proton channel (Du et al, 2010Huang et al, 2008;Wang et al, 2009a;Wei et al, 2009) based on the original NMR findings as reported in Pielak et al (2009) and Schnell and Chou (2008). Our group has even built molecular models of HIV-1 co-receptor CCR5 (Yang and Liu, 2000), fibrinogen receptor, ADP receptor, recombinant SCF-MCSF (stem cell factor-macrophage colony stimulating factor) fusion proteins and their receptors (Chen et al, 2005), and some pentapeptides with higher alpha-helical tendency using the same method, especially integrin GPIIB (Yang et al, 2004) and purinergic receptor P2Y12 (Zhan et al, 2007) were embodied into PDB database, and their PDB codes were 1UV9 and 1VZ1, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al have done many studies of molecular modeling on the metabolizing activity enzymes, such as NAD(P)Hdependent d-xylose reductase, P450s, xylose reductase, and they mainly focus on the binding interaction [83][84][85][86][87][88][89][90]. According to the resolved NMR structures [91,92], influenza A viruses can undergo changes, which may result in extremely toxic and drug resistance,.…”
Section: Cheminformatics Used In the Research Of Hces1mentioning
confidence: 99%